Promoting responsive care and early learning practices among caregivers of children 0-23 months in the Kyrgyz Republic: findings from integrating a counselling intervention with nutrition services - Lesley Oot; Veronica Varela; Cholpon Abdimitalipova; Marie Paul Nisingizwe; Kristen Cashin; Begimai Zhumgalbekova; Kelsey Torres; Malia Uyehara; Kathryn Beck; Tim Williams; Nazgul Abazbekova; Saikalbubu Bozova; et al. (Cambridge University Press, 2024)
Abstract Objective: To assess changes in caregiver practices for young children after integrating the Responsive Care and Early Learning (RCEL) Addendum package into nutrition services after 10 months of implementation. Design: We measured changes in RCEL practices through a pre- and post-intervention assessment comprising a household survey and observations. To implement the intervention, we trained health service staff and community volunteers to deliver RCEL counselling to caregivers of children 0-23 months of age through existing community and facility-level platforms. Setting: Jalal-Abad and Batken regions in the Kyrgyz Republic. Participants: Caregivers of children aged 0-23 months at baseline. Results: We found statistically significant increases in RCEL practices, availability of early learning opportunities in the home, decreases in parenting stress and improvements in complementary feeding practices after the intervention implementation period. Conclusions: Findings show that delivery of RCEL counselling using the RCEL Addendum was associated with improved responsive care practices and early learning opportunities. We also found that integration of RCEL with infant and young child feeding counselling did not disrupt nutrition service delivery or negatively affect complementary feeding outcomes, but rather suggest synergistic benefits. Given the importance of providing holistic care to support optimal early childhood development, these findings provide new evidence on how to strengthen the delivery of nurturing care services in the Kyrgyz Republic.